A participação dos usuários no desenvolvimento de sistemas de informação - Furnival, Ariadne Chloe Mary (Universidade Federal de São Carlos, 1995)
As abordagens tradicionais de design de sistemas de informação (SIs) computadorizados fundamentam-se em certos pressupostos técnicos que geralmente não englobam fatores sociais e psicológicos da organização na qual o novo sistema será implantado. Os custos de se ignorar tais fatores são as vezes altos, pois usuários insatisfeitos podem resistir ao uso do sistema, ou usá-lo de uma maneira diferente daquela para a qual foi originalmente projetado. As limitações das metodologias de design tradicionais têm sido mitigadas pela adoção de metodologias soft, que baseiam-se na ideia de que somente a participação contínua dos usuários no desenvolvimento do novo sistema pode evitar problemas futuros, pois são os usuários - e não o analista - que detêm o conhecimento especializado do seu trabalho, o que é necessário para a construção de um sistema de alta qualidade e, portanto, produtivo.

The traditional approaches to the design of computerized information systems are grounded in certain technical presuppositions that are usually unable to take on board social, political and psychological aspects of the organization in which the new system will be implemented. The costs of ignoring these dimensions can sometimes be high, since dissatisfied users can resist use of the system, or use it in ways not forseen by the original design of the system. The limitations of the traditional, so-called “hard” approaches to design have been mitigated by the emergence and adoption of radically different, “soft” methodologies, which are based on the central idea that only the continued participation of the users in the system’s development can avoid future problems, given that only the users - and not the systems analyst - possess the specialist knowledge pertaining to the nature of their work that is necessary to construct a high quality, and therefore productive, system.
The participation of users in the development of information systems
Keywords: Sistemas de informação; Participação de usuários; Information systems development; User participation